Distinct resting state neural activity in chronic pain patients who respond to transcranial electric stimulation for pain relief - Fernández, Alba; Rubal-Otero, Lara; Gil-Ugidos, Antonio; Pinal, Diego; González-Villar, Alberto Jacobo; Carrillo-de-la-Peña, María Teresa (Frontiers in Human Neuroscience, 2025)
IntroductionTranscranial electric stimulation (tES) techniques have shown promising results for pain relief in chronic pain. However, little is known about the mechanisms by which these non-invasive neuromodulation techniques produce analgesic effects. Besides, previous studies underscore the need to identify profiles of patients with a better response to tES.MethodsIn this randomized clinical trial (ClinicalTrials.gov: NCT05099406), we studied whether tES modulate brain oscillatory activity by recording resting state EEG (eyes open) from 106 chronic pain patients before and after a 15-day home-based intervention with either transcranial direct or alternate current stimulation, or sham stimulation. Power spectral density (PSD) at rest was analyzed in the theta, alpha, and beta frequency bands, in two 2 × 2 designs with the factor time (pre vs. post intervention session) and group, with each active tES condition being compared against the sham stimulation. Additionally, we compared responders vs non-responders to active tES (according to their reported pain relief after the intervention) in the same PSD indices.ResultsThe analysis showed that the intervention had no significant effects on PSD in any band, and thus revealed that understanding the physiological mechanisms of the analgesic effects of tES remains a pending matter. However, higher PSD in the theta band was observed for responders compared to non-responders regardless of the assessment session.DiscussionThis finding suggests that the theta-band oscillatory activity of patients with chronic pain could be a promising prognostic biomarker for the effectiveness of tES and opens a new avenue for individualizing tES interventions.